Acquisition of Leadership Skills at the Primary Stage - Dwivedi, Ruchi (THE PRIMARY TEACHER, 2017)
Primary school students evolve constantly as they are in the formative stage of their lives. Apart from being imparted basic education, they need to be trained in leadership skills from an early age. Therefore, the teaching fraternity needs to put in conscious effort to develop leadership skills in the students. The acquisition of leadership skills helps enhance the students’ academic, as well as, social performance. These skills enable them to learn the art of sustaining and nurturing relationships, defining identities, problem-solving, and thereby, achieving the desired goal. Taking this into consideration, this paper tries to analyse different leadership skills at the cognitive domain, which play a critical role in the overall development of students at the primary stage.